Jasara Simon: capstone - Simon, Jasara, artist (Colorado State University. Libraries, 2013)
The artist's statement: Much of my inspiration comes from the world that surrounds me. I explore physical wonder of natural forms, as well as my own immersion into spirituality and spiritual art forms. Through my art I aim to connect these two concepts, incorporating natural imagery in both my jewelry and photographic work in conjunction with the human form. By doing so I convey my own belief in our physical and spiritual connection with our earth. In my metal work I do this through incorporating stones and crystals, which I believe to have healing and metaphysical properties, into the natural flow of my designs. In my "Moon-Phase" piece for example, I use the phases of the moon as well as a moonstone to illustrate phases of change and growth; just as our moon goes through phases of change, so do we. The metaphysical properties of moonstone are said to be extremely powerful, especially for women, aiding in intuitive sensitivity as well as helping to increase one's ability to be flexible and flow with life. By connecting both material and imagery I express my desire to flow with the changes and phases of my life, experiencing more balance and harmony with myself and the world. This same idea can be found in my photographic work, in which I have merged the female form with close up nature scenes. By blending these images together I want to directly express my feelings of unity with our earth and the spiritual bond that all humans have with our universe. Throughout all my work I remind the viewer of this deep connection which often tends to get lost in the bustle of everyday life. In doing so I create an understanding that we are not separate from our earth; thus we must develop a greater sense of responsibility in taking care of our home and preserving its natural beauty.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: photo image making